Potential for Rehabilitation Management Utilizing A Theory of Planned Behavior Approach Via Telehealth in Home Treatment-Based Diabetes Management: A Literature Review - Wildana, Fahmi; Lutfian; Azizah, Aufa; Oktaviana, Essarani (Jurnal Ilmiah Kesehatan, 2024)
iabetes Mellitus is a metabolic disorder characterized by insufficient insulin production or ineffective utilization of insulin, resulting in elevated blood glucose levels. The prevalence of Diabetes Mellitus continues to rise annually, highlighting the urgent issue of inadequate blood sugar control among diabetic patients. Ineffective management of blood glucose levels poses significant risks for complications and adversely affects the quality of life of individuals with diabetes. This article employs a literature review methodology to explore the potential of rehabilitation management for diabetic patients. A comprehensive literature search was conducted across various databases, including Google Scholar, Science Direct, PubMed, and ProQuest. The search utilized keywords such as "Diabetes Mellitus," "Theory of Planned Behavior," "Rehabilitation of Diabetic Patients," and "Telehealth." The inclusion criteria encompassed publications in both Indonesian and English languages from 2016 to 2021. Eligible publications were identified and analyzed using the PRISMA method for synthesis. Rehabilitation interventions for diabetic patients focus on utilizing resources available within the home environment. These interventions have demonstrated a significant impact on various aspects of lifestyle, including physical activity, medication adherence, health education, and psychological support. Furthermore, telehealth has emerged as an effective medium for delivering remote health interventions, facilitating improved patient engagement and outcomes. In the context of the Social 5.0 era, telehealth presents a promising alternative for home-based rehabilitation of diabetic patients. By leveraging patient resources, telehealth can enhance the effectiveness of diabetes rehabilitation care and improve overall health outcomes for individuals living with diabetes.